(untitled) (Bangladesh Medical Journal Khulna, 2016)
There are few case reports regarding star fruit’s nephrotoxicity and neurotoxicity in chronic kidney disease patients. Recently cases are found in people with normal renal function Star fruit nephrotoxicity is believed to be due to its high oxalate content which causes acute obstructive oxalate nephropathy. A neurotoxin (caramboxin) present in the fruit is responsible for neurotoxic features. Here we present a young male who developed acute kidney injury following star fruit ingestion in empty stomach. After admission, patient was treated conservatively and recovered completely. Bang Med J (Khulna) 2015; 48 : 37-39